PENERAPAN E-GOVERNMENT SISTEM INFORMASI PELAYANAN PERLINDUNGAN PEREMPUAN DAN ANAK DI KELURAHAN PUTAT JAYA - Mohamad Geoveza Putra Syahtoni; Oktarizka Reviandani (Journal Publicuho, 2024)
The aim of this research is to determine the implementation of the Women and Child Protection Services Information System (SIAP-PPAK) in Putat Jaya Village. Women and Child Protection Services Information System is a website-based application designed as a one click for all solution to integrated women's, children's and family problems. The idea for this e-Government innovation came from the Department of Women's Empowerment and Child Protection and Population Control and Family Planning (DP3APPKB) of Surabaya City. This study used descriptive qualitative method. The data collection technique is carried out through data triangulation which combines interviews, observation, literature study and documentation. The research results show that the implementation of SIAP-PPAK in Putat Jaya Subdistrict has been carried out well by fulfilling the six (6) indicators of the Van Meter and Van Horn theoretical models. Although, there are still several obstacles, these can be overcome so that women and child protection services using SIAP-PPAK can be provided with quality.